Smarter US modernization, without new nuclear weapons. (2nd January 2019) - Weber, Andrew; Parthemore, Christine
ABSTRACT: The current US nuclear modernization program departs in several major ways from longstanding US nuclear policy: It elevates the role of nuclear weapons in US national security strategy, includes plans for developing several new nuclear weapon capabilities, and resurrects former nuclear capabilities that past US presidents had wisely eliminated. Of all the Trump administration's nuclear modernization plans, however, the most destabilizing are probably the new, low-yield nuclear options and dual-capable systems that may be ambiguously nuclear or conventional. But the United States can still return to a smarter path – one that eliminates these specific nuclear weapons plans, and adopts a more measured nuclear rhetoric to match.